2021
DOI: 10.3389/fpsyg.2020.605724
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Emotion Recognition Ability Is Unaffected by Stereotype Threat

Abstract: Eliciting negative stereotypes about ageing commonly results in worse performance on many physical, memory, and cognitive tasks in adults aged over 65. The current studies explored the potential effect of this “stereotype threat” phenomenon on older adults’ emotion recognition, a cognitive ability that has been demonstrated to decline with age. In Study 1, stereotypes about emotion recognition ability across the lifespan were established. In Study 2, these stereotypes were utilised in a stereotype threat manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…At the automatic stage of visual search of emotional stimuli, older but not younger adults were faster to detect emotionally negative, high-arousal targets ( Leclerc and Kensinger, 2008 ). Another study demonstrated that older adults’ performance in recognizing facially expressed emotions were not affected by stereotype (ageism) threat, likely because emotion recognition is automatic and less susceptible to the cognitive load posed by the threats ( Atkinson et al, 2020 ). Notably, a recent study reported positive versus negative categorization of faces of ambiguous valence to be faster in older and slower in young adults, and discussed role of information processing automaticity in manifesting the positivity effect ( Petro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the automatic stage of visual search of emotional stimuli, older but not younger adults were faster to detect emotionally negative, high-arousal targets ( Leclerc and Kensinger, 2008 ). Another study demonstrated that older adults’ performance in recognizing facially expressed emotions were not affected by stereotype (ageism) threat, likely because emotion recognition is automatic and less susceptible to the cognitive load posed by the threats ( Atkinson et al, 2020 ). Notably, a recent study reported positive versus negative categorization of faces of ambiguous valence to be faster in older and slower in young adults, and discussed role of information processing automaticity in manifesting the positivity effect ( Petro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%